Tea fit for a queen : recipes & drinks for afternoon tea - Fortes, Imogen; Fortes, Imogen (Ebury Press, 2014)
Filled with recipes that have stood the test of time as well as fascinating anecdotes and tales, Tea Fit for a Queen reveals how the tradition of afternoon tea started in royal Britain. Over 40 charming recipes include everything from delicate finger sandwiches to Victoria sponge cake, Chelsea Buns and a Champagne Cocktail. In these pages learn about the infamous royals and their connection to the history of tea; why jam pennies were Queen Elizabeth II's favourite tea time treat and how mead cake came to be served during Henry VIII's reign. Discover what cake William and Catherine selected for their wedding and hear why orange-scented scones became a royal tradition at Kensington Palace. Tea Fit for a Queen presents a taste of palace etiquette to take home.